# |
ODE |
Mathematica |
Maple |
\[
{}x y^{\prime }-y = x \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y \ln \left (y\right ) = x y \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (-a^{2}+x^{2}+y^{2}\right )+y \left (x^{2}-y^{2}-b^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+x^{2}+y^{2}}{2 x y}
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}y+\left (a \,x^{2} y^{n}-2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 x^{2} y+{\mathrm e}^{x}\right )-\left ({\mathrm e}^{x}+y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{x^{\prime }}^{2} = k^{2} \left (1-{\mathrm e}^{-\frac {2 g x}{k^{2}}}\right )
\] |
✗ |
✓ |
|
\[
{}y y^{\prime }+b y^{2} = a \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x -2 y}+x^{2} {\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+x -\left (2 x^{2}+2 y^{2}-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y+3 x y^{\prime }+2 x y \left (3 y+4 x y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \left (1+\frac {1}{x}\right )+\cos \left (y\right )+\left (x +\ln \left (x \right )-x \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +2 y+3\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (2 \ln \left (x \right )+1\right )}{\sin \left (y\right )+y \cos \left (y\right )}
\] |
✓ |
✓ |
|
\[
{}s^{\prime }+x^{2} = x^{2} {\mathrm e}^{3 s}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y} \left ({\mathrm e}^{x}-{\mathrm e}^{y}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x +y\right )+\cos \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {\tan \left (y\right )}{x} = \frac {\tan \left (y\right ) \sin \left (y\right )}{x^{2}}
\] |
✓ |
✗ |
|
\[
{}x^{2}-a y = \left (a x -y^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \left (2 x y+{\mathrm e}^{x}\right )-{\mathrm e}^{x} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\left (-x^{2}+1\right )^{{3}/{2}}} = \frac {x +\sqrt {-x^{2}+1}}{\left (-x^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y-x y^{\prime }+x^{2}+1+x^{2} \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sec \left (y\right )^{2} y^{\prime }+2 x \tan \left (y\right ) = x^{3}
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+\frac {a x +b y+c}{b x +f y+e} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-7 y^{\prime }+12 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-5 y^{\prime }+6 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-9 y^{\prime }+18 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 x y^{\prime }-3 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 y^{\prime } y \cot \left (x \right ) = y^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 y^{\prime } \cosh \left (x \right )+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (y^{\prime }-y\right ) = x \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}x +y {y^{\prime }}^{2} = y^{\prime } \left (x y+1\right )
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (y-x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-a \,x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x y^{\prime }+y y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-y^{\prime } \left (y^{2}+x y+x^{2}\right )+x y \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{\prime }+y+x \right ) \left (y+x +x y^{\prime }\right ) \left (y^{\prime }+2 x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{3}+y \left (1+x^{2} y\right ) {y^{\prime }}^{2}+y^{\prime } y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x y y^{\prime }-6 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x {y^{\prime }}^{2}-y^{2} {y^{\prime }}^{2}-2 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (2-3 y\right )^{2} = 4-4 y
\] |
✓ |
✓ |
|
\[
{}y = 3 x +a \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y = x +a \arctan \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}3 {y^{\prime }}^{5}-y y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+a x = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{\prime } = {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y = \sin \left (y^{\prime }\right )-y^{\prime } \cos \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = \sin \left (x \right ) y^{\prime }+\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } \tan \left (y^{\prime }\right )+\ln \left (\cos \left (y^{\prime }\right )\right )
\] |
✓ |
✓ |
|
\[
{}x = y y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (2 x -b \right ) y^{\prime } = y-a y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x = y+a \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}x \left (1+{y^{\prime }}^{2}\right ) = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} = a^{2} \left (1+{y^{\prime }}^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {a}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+a y^{\prime } \left (1-y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {b^{2}-a^{2} {y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (-x y^{\prime }+y\right ) \left (y^{\prime }-1\right ) = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-y y^{\prime }+a = 0
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } \left (x -b \right )+\frac {a}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}4 y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x +\frac {y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}} = a
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+2 y^{2} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+x \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}x +y^{\prime } y \left (2 {y^{\prime }}^{2}+3\right ) = 0
\] |
✗ |
✓ |
|
\[
{}y = \frac {2 a {y^{\prime }}^{2}}{\left (1+{y^{\prime }}^{2}\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = a \left (1+{y^{\prime }}^{2}\right ) \left (x^{2}+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✗ |
|
\[
{}4 x {y^{\prime }}^{2}+4 y y^{\prime } = y^{4}
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}-\left (2 x +4 \sin \left (x \right )-\cos \left (x \right )\right ) {y^{\prime }}^{2}-\left (x \cos \left (x \right )-4 x \sin \left (x \right )+\sin \left (2 x \right )\right ) y^{\prime }+\sin \left (2 x \right ) x = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = {y^{\prime }}^{2}-\frac {2 y y^{\prime }}{x}+1
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = x +y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}a^{2} y {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (-x y^{\prime }+y\right ) = y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({y^{\prime }}^{2}-\frac {1}{a^{2}-x^{2}}\right ) \left (y^{\prime }-\sqrt {\frac {y}{x}}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (-a^{2}+x^{2}\right )-2 x y y^{\prime }+y^{2}+a^{4} = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+y^{\prime } \left (3 x^{2}-2 y^{2}\right )-6 x y = 0
\] |
✓ |
✓ |
|
\[
{}2 y = x y^{\prime }+\frac {a}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = a y^{\prime }+\sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (a {y^{\prime }}^{2}-b \right ) x y+\left (b \,x^{2}-y^{2} a +c \right ) y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}y = a y^{\prime }+b {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (y+2 x -{\mathrm e}^{x -y}\right ) {y^{\prime }}^{2}+\left (2 x y-2 x \,{\mathrm e}^{x -y}-y \,{\mathrm e}^{x -y}\right ) y^{\prime }+2 x y \,{\mathrm e}^{x -y} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+6 y^{2}-3 x^{2} y\right ) y^{\prime } = 3 x y^{2}-x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{3} y^{3}+x^{2} y^{2}+x y+1\right ) y+\left (x^{3} y^{3}-x^{2} y^{2}-x y+1\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (\frac {y}{x}\right )+y \sin \left (\frac {y}{x}\right )\right ) y = \left (y \sin \left (\frac {y}{x}\right )-x \cos \left (\frac {y}{x}\right )\right ) x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x +y y^{\prime }\right ) = h^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{2}-3 x y y^{\prime } = 2 y^{2}+x^{3}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+a x = 0
\] |
✓ |
✓ |
|